Implementasi IoT Pengontrolan Pupuk NPK Untuk Sayur Organik Dengan Metode Vertical Garden Menggunakan Mikrokontroler ESP32 Berbasis Android (Studi Kasus: Villa Rizki Ilhami) - Aji Saputra; Hadi Zakaria (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
In connection with the increasing need for human food such as organic vegetables, it is not balanced with adequate land. This gave rise to the idea of using a small area of land but still being able to have a garden full of plants. Vertical gardens are the right solution for narrow land, with current technological advances managing plants will feel easy if it can be done using tools. With limited time and space to manage plants. Therefore, to solve these problems we need a tool that can control plant fertilizers via the internet so that it can be controlled remotely. The development of this research uses the Waterfall model because the model is easy to implement and appropriate to use in building an application. Making a plant fertilizer control tool using Arduino ESP32 with Firebase which is used as a database server.